Classification of spinopelvic balance in ambulatory adolescents and adults with cerebral palsy: a cross-sectional study - Emmanuelle Chaléat-Valayer; Carole Vernez; Stéphane Verdun; Soline Bellaiche; Laure Mathevon; Rachel Bard Pondarré; Hovannes Agopyan; Marianne Bagnol; Kariman Abelin (Scientific Reports)
Abstract We aimed to determine the spinopelvic profile types of ambulatory adolescents and adults with diplegic CP, and their relationship with functional ability (Gross Motor Function Classification System [GMFCS]), pain, and previous orthopaedic treatments. We measured anatomical variables on radiographs from 77 individuals with CP (mean age, 28.4, SD, 11.9 years), GMFCS levels I–III. We applied a non-supervised hierarchical ascendant classification followed by k-medoids analysis to 5 key anatomical variables. We compared radiological and clinical variable values between the spinopelvic profiles identified. Three spinopelvic profiles emerged, according to whether the pelvis was anteverted (sacral slope ≥ 38°) or retroverted (< 38°) and whether this was concordant with the pelvic incidence (≥ 54° for anteversion and < 54° for retroversion). Most (61/77, 79%) participants had anteversion, concordant for only 28/61 (46%); 16/77 (21%) had retroversion, concordant for 14/16 (88%). More participants with concordant anteversion experienced pain than participants with discordant anteversion (P = 0.03). Rates of previous treatments did not differ between concordant and discordant anteversion. More participants with GMFCS level III had discordant anteversion than those with levels I–II (P = 0.02). Categorising the spinopelvic profile is the first step to understanding pain causes and proposing targeted interventions and/or rehabilitation programs.